REACH Story of Change: Improving water security in Ethiopia through integrated use of surface and groundwater resources - REACH (University of Oxford, 2024)
As one of Africa’s fastest growing cities, Addis Ababa’s demand for water has sky-rocketed over recent decades due to population growth, increased per capita consumption, rural to urban migration, and growing water demand from industry. Water supplies across the city are already struggling to meet demand, with regularly interruptions to water services exacerbating inequities.